2011
DOI: 10.1098/rspb.2011.1282
|View full text |Cite
|
Sign up to set email alerts
|

Vector host-feeding preferences drive transmission of multi-host pathogens: West Nile virus as a model system

Abstract: Seasonal epizootics of vector-borne pathogens infecting multiple species are ecologically complex and difficult to forecast. Pathogen transmission potential within the host community is determined by the relative abilities of host species to maintain and transmit the pathogen and by ecological factors influencing contact rates between hosts and vectors. Increasing evidence of strong feeding preferences by a number of vectors suggests that the host community experienced by the pathogen may be very different fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
176
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(179 citation statements)
references
References 63 publications
(94 reference statements)
2
176
1
Order By: Relevance
“…In addition, the Park: Water microhabitat type, which had the highest probability of seropositive birds, also had the highest WNV amplification fraction (80%) from American robins, with less than 6% of amplification from northern cardinals and song sparrows combined. Taken together, these results suggest that the absence of American robins, which have been considered "superspreaders" of WNV elsewhere, 13,14,37,45 combined with WNV amplification arising predominantly from northern cardinals and song sparrows, may be responsible for diminished WNV transmission in the urban forest patch microhabitats.…”
mentioning
confidence: 83%
“…In addition, the Park: Water microhabitat type, which had the highest probability of seropositive birds, also had the highest WNV amplification fraction (80%) from American robins, with less than 6% of amplification from northern cardinals and song sparrows combined. Taken together, these results suggest that the absence of American robins, which have been considered "superspreaders" of WNV elsewhere, 13,14,37,45 combined with WNV amplification arising predominantly from northern cardinals and song sparrows, may be responsible for diminished WNV transmission in the urban forest patch microhabitats.…”
mentioning
confidence: 83%
“…Other related flaviviruses such as dengue virus, Zika virus and HCV are also human pathogens of public health relevance. While the transmission of WNV between hosts has been modelled [54][55][56][57], little attention has been paid to modelling the within-host dynamics of WNV. Here we have modified a within-host model first developed for influenza A infection [30] in order to describe WNV infection in mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous studies have revealed an important interplay between host compatibility and the encounter rate in driving pathogen transmission dynamics over time [3], space [5] and between ecological communities that differ in structure [4,67]. Indeed, host range expansions also depend on the compatibility of novel hosts toward those parasites, and will not proceed if new host-parasite combinations are incompatible.…”
Section: Quiscalus Quiscula C U L E X P I P I E N S C U L E X R E S Tmentioning
confidence: 99%
“…Mosquitoes, which are important vectors for a diversity of pathogens, are known to feed heterogeneously across hosts by using some species disproportionately, relative to their abundance [13][14][15]. This heterogeneity in mosquito-feeding patterns can strongly influence disease transmission dynamics [3,4,13,16]. Mosquito-feeding networks may also be compartmentalized [17], with certain vector species using a distinct subset of available host species [14,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation